Impact of Environmental Standards on Employment - TAZHBAYEVA, Ainagul; AIMAGAMBETOV, Yerkara; TAZHBAYEV, Nurlan; GRELA, Manuel Fernandez (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
There is a wide variety of dynamics of structural transformations of employment in the world. Some regions of the world are seeing steady growth in employment, while others are facing severe declines in employment. Demographic changes potentially affect regional growth through a reduction in the labor force, which has an impact on growth and is largely dependent on the level of education, labor productivity, and labor resources. The article discusses the impact of ecology on the structural transformation of employment in the Republic of Kazakhstan. The labor market of the Republic of Kazakhstan has acquired a permanent character over the years of Independence and reflects the changes that the country's economy has experienced over the past 30 years. Structural shifts were observed in the structure of world GDP from industrial production to the service sector, to the developing economy of Kazakhstan. The purpose of the study is to analyze the impact of ecology on the structural transformation of employment in the context of digitalization of the economy of Kazakhstan.